Solar sail trajectory optimization for interplanetary missions: part ii—neuro-fuzzy control - Varatharajoo, Renuganth; Chak, Yew Chung; Razoumny, Vladimir (Springer Science and Business Media Deutschland GmbH, 2025)
This paper presents the development and validation of a neuro-fuzzy controller designed to approximate optimal solar sail steering laws for interplanetary transfers. An Adaptive Neuro-Fuzzy Inference System (ANFIS) is trained using data obtained from offline trajectory optimization. The controller structure, rule base reduction using fuzzy subtractive clustering, and performance characteristics are detailed. Numerical simulations of Earth–Mars and Earth–Venus transfers demonstrate the neuro-fuzzy controller’s capability to approximate the optimal control performance with high accuracies. These results highlight the potential of neuro-fuzzy control approaches for the real-time autonomous guidance of solar sail missions.